Long-chain bases, phosphatidic acid, MAPKs, and reactive oxygen species as nodal signal transducers in stress responses in Arabidopsis - Saucedo-García, Mariana; Gavilanes-Ruíz, Marina; Arce-Cervantes, Oscar (Frontiers in Plant Science, 2015)
Due to their sessile condition, plants have developed sensitive, fast and successful ways to contend to environmental changes. These mechanisms operate as informational wires conforming extensive and intricate networks that are connected in several points. The responses are designed as pathways orchestrated by molecules that are transducers of protein and non-protein nature. Their chemical nature imposes selective features such as specificity, formation rate and generation site to the informational routes. Enzymes such as mitogen-activated protein kinases (MAPK) and non-protein, smaller molecules, such as long chain bases, phosphatidic acid and reactive oxygen species are recurrent transducers in the pleiotropic responses to biotic and abiotic stresses in plants. In this review, we considered these four components as nodal points of converging signaling pathways that start from very different stimuli and evoke very different responses. These pleiotropic effects may be explained by the possibility that every one of these four mediators can be expressed from different sources, cellular location, temporality or magnitude. Here, we review recent advances in our understanding of the interplay of these four specific signaling components in Arabidopsis cells, with an emphasis on drought, cold and pathogen stresses.